2014
DOI: 10.1113/expphysiol.2014.080093
|View full text |Cite
|
Sign up to set email alerts
|

Ankle dorsiflexor muscle size, composition and force with ageing and chronic obstructive pulmonary disease

Abstract: Loss of skeletal muscle strength is a well-recognized feature of ageing and chronic obstructive pulmonary disease (COPD). Reductions in muscle size provide only a partial explanation for this loss of strength, and additional contributory factors remain undetermined. We hypothesized that reductions in skeletal muscle strength, as measured in the ankle dorsiflexor muscles, would be reduced with ageing and COPD as a result of changes in both size and composition of the tibialis anterior muscle. Twenty healthy you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
(115 reference statements)
1
27
0
Order By: Relevance
“…Mechanical unloading due to physical inactivity contributes to peripheral muscle abnormalities and dysfunction. Muscle weakness in COPD has been reported primarily in thigh musculature (quadriceps, in both men and women [41]), and more recently documented in the ankle dorsiflexors and plantarflexors [42,43]. Taken together, these abnormalities indicate an overall decline in both the contractile and oxidative capacity of lower limbs muscles in patients with COPD [11].…”
Section: Source Of Gait Abnormalities In Copdmentioning
confidence: 82%
“…Mechanical unloading due to physical inactivity contributes to peripheral muscle abnormalities and dysfunction. Muscle weakness in COPD has been reported primarily in thigh musculature (quadriceps, in both men and women [41]), and more recently documented in the ankle dorsiflexors and plantarflexors [42,43]. Taken together, these abnormalities indicate an overall decline in both the contractile and oxidative capacity of lower limbs muscles in patients with COPD [11].…”
Section: Source Of Gait Abnormalities In Copdmentioning
confidence: 82%
“…Previous studies from this laboratory and others have demonstrated relationships between muscle size and strength in the knee extensor and ankle dorsiflexor muscles of COPD patients and age‐matched controls. Nonetheless, muscle CSA does not fully account for variation in muscle strength.…”
Section: Discussionmentioning
confidence: 77%
“…Differences in ADMF and architecture parameters between testing occasions were determined with Wilcoxon signed‐rank tests. Predicted values and cutoffs for 100‐H Z AD were determined from a regression model derived in similarly aged healthy controls: 100‐H Z AD (kg) = 4.431 + −0.116age + 0.030TA CSA − 0.389 if female. Muscle weakness in critically ill patients was defined as 1.645 residual SD below the predicted value derived from 100‐H Z AD responses from healthy individuals.…”
Section: Methodsmentioning
confidence: 99%
“…A frequently discussed issue is weakening of the thigh muscles, particularly changes in the vastus lateralis muscle (Seymour et al, 2010;Shrikrishna et al, 2012). Even more significant dysfunction affects the distal muscles of the lower limb, especially the tibialis anterior muscle (Gagnon et al, 2013;Maddocks, Jones, et al, 2014). It was confirmed that a loss of intramuscular fat significantly decreases exercise tolerance.…”
Section: Resultsmentioning
confidence: 99%